PI/NCC-based carbon molecular sieve membranes for hydrogen purification : effect of aging times - Norazlianie, Sazali; W. N. W., Salleh; Siregar, J. P.; M. H. D., Othman; J., Jaafar; T., Gunawan (IOP Publishing, 2020)
In this study, the effect of stabilization temperature on the performance of tubular carbon Upgrade the gas separation performance of the resultant carbon molecular sieve (CMS) membrane, a synthesized nanocrystalline cellulose (NCC) utilizing tissue paper as an added substance was included into the simpleton arrangement at pyrolysis temperatures of 800°C. This paper shows the inference of CMSs from BTDA-TDI/MDI polyimide (PI) arranged by means of a dip-coating strategy on an inorganic cylindrical help surface, trailed by a heat treatment (adjustment and carbonization) under Ar gas stream. Extraordinary consideration was given to the physicochemical attributes of the subsequent PI/NCC-based CMS and its comparing gas permeation properties. Pure gas permeation tests were performed utilizing H2, and N2 at room temperature. The gas permeation information showed that the CMS displayed an amazing performance contrasted with the polymeric membrane. Upgrade in the two gas permeance and selectivity were watched arranged with fresh CMS membrane, with H2N2 selectivity of 434.68±1.39, regarding the neat CMS. By controlling different aging times (fresh, 1 day, multi week, and 3 months), CMSs with various structures and properties were gotten.